2017
DOI: 10.5964/ejop.v13i3.1327
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the transition to adulthood, developmental features of emerging adulthood, and views of the future among Greek studying youth

Abstract: This study investigated emerging adulthood and transition to adulthood in Greece, a highly underresearched issue in this country. Participants were 784 university students aged 17.5-27.5 years. Criteria for the transition to adulthood, developmental features of emerging adulthood, perceived adult status, views of the future (optimism), and sociodemographic variables were assessed. The results support the existence of emerging adulthood as a distinct life period in Greece. More than two thirds of the sample wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 39 publications
7
28
0
15
Order By: Relevance
“…For example, individualistic criteria were found to be prominent in one study which presented data collected before the beginning of the financial crisis and in which no factor analyses were performed (Petrogiannis, 2011). In contrast, factors representing a mixture of individualistic and collectivistic criteria emerged as the predominant conception of adulthood in another study (Galanaki & Leontopoulou, 2017). In addition, another recent Greek study (Vleioras & Mantziou, 2017) showed that the achievement of two role transitions, that is, marriage and semiautonomous and independent living, decreased the feeling of being an emerging adult only after the age of 30 and only for women, whereas it had no effect on people aged 25-29.…”
Section: Emerging Adulthood and Transition To Adulthood In Greecementioning
confidence: 89%
See 2 more Smart Citations
“…For example, individualistic criteria were found to be prominent in one study which presented data collected before the beginning of the financial crisis and in which no factor analyses were performed (Petrogiannis, 2011). In contrast, factors representing a mixture of individualistic and collectivistic criteria emerged as the predominant conception of adulthood in another study (Galanaki & Leontopoulou, 2017). In addition, another recent Greek study (Vleioras & Mantziou, 2017) showed that the achievement of two role transitions, that is, marriage and semiautonomous and independent living, decreased the feeling of being an emerging adult only after the age of 30 and only for women, whereas it had no effect on people aged 25-29.…”
Section: Emerging Adulthood and Transition To Adulthood In Greecementioning
confidence: 89%
“…The factors were labeled family capacities, norm compliance, age/biological transitions, financial independence, and relational maturity and were similar, although not identical, to those found in the aforementioned three studies (see Table 4). More specifically, the main divergence from the factor structures that have emerged in several studies up to now is the financial independence factor (found only in Greece by Galanaki & Leontopoulou, 2017 and in Romania by Nelson, 2009). It represents a conception of adulthood as a time of financial independence after the end of education and the establishment of a permanent full-time job, which enables the individual to purchase a house, live independently, and form a family.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies conducted in the United States (Nelson and Barry 2005), Western Europe (Sirsch et al 2009), Southern Europe (Galanaki and Leontopoulou 2017), and Central Europe (Oleszkowicz and Misztela 2015;Macek et al 2007) also suggest that the majority of people at the age of 20-something do not consider themselves as entirely adult. Arnett (2000) called this group of young people, especially those in their twenties, 'emerging adults'.…”
Section: Role Transitions In Emerging Adulthoodmentioning
confidence: 99%
“…This period is associated with developmental challenges, difficult in some cases, but with great heterogeneity per context, mainly due to socio-cultural differences. It occurs mainly in developed modern societies, which provide the opportunity to explore different alternative routes in their lives (Galanaki & Leontopoulou, 2017-Galanaki & Sideridis, 2018-Leontopoulou, Mavridis, & Giotsa, 2016-Petrogiannis, 2011. It becomes clear, therefore, that the university, as a social context in which the student lives and works, plays a decisive role, especially in Greece, where the majority of young people study in higher education (Raikou, 2019).…”
Section: Introductionmentioning
confidence: 99%